Karakteristik Mutu Kadar air , kadar abu dan Organoleptik pada Penyedap Rasa instan - Rosdiani Azis; Ingka Rizkyani Akolo (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2019)
Flavoring is a product that is absolutely needed in people's lives today. The fact is that there are now many foods that contain unhealthy flavoring, especially MSG, Nike and anchovy have high levels of glutamate acid, so Nike and anchovy can be used as raw materials for natural flavoring. The purpose of this study is to determine the factors that provide optimal results on the quality of instant flavorings produced and determine the effect of drying time, drying temperature and type of fish used on water content, ash content of organoleptic properties of instant flavoring. This study uses the Taguchi method design with 3 factors and mixed levels (2 and 4 levels) to optimize product and process design so that an optimal response is produced. The factors used are Drying Time (A), Drying Temperature (B), and Fish Type (C). The drying time used is 7 hours (A1); 8 hours (A2); 9 hours (A3) and 10 hours (A4). Drying temperatures used are: 500 (B1) and 600 (B2), while the types of fish used are wet anchovies (C1) and nike fish (C2). While the response variables used to determine the quality of instant flavorings are water content, ash content and organoleptic properties. Organoleptic quality response and shelf life will be determined by the optimization objectives in the Minitab program 16. The results of the research produced the best flavoring seen from water content is flavoring from Nike fish with a drying time of 10 hours and drying temperature of 800C, whereas if viewed from ash content, then the best flavoring is the flavoring of nike fish with a drying temperature of 800C and a long drying time of 8 hours